Feasibility for value addition to sucrose in South Africa through conversion to platform chemicals - Jegede, Kemi (Centre for Bioprocess Engineering Research, 2019)
The world sugar price is constantly changing in response to supply and demand and is currently very low as compared to the prices it is sold at domestically in South Africa. The drop in the worldwide price of sugar is due to its oversupply as yields of sugar production have increased in recent years and subsidies and protection measures in other producing countries. The low prices also mean imports are cheaper than local sugar. This pushes down the average sugar price and leads to a low profit margin. Further, sugar production in South Africa is facing a number of challenges. The industrialization of the sugar belt in KwaZulu-Natal has resulted in less plantations and challenging topography for these. Incentivisation of small, medium and micro-scale commercial operations has increased the number of smaller scaled operations, with less economy of scale and less capital backing. Climatic factors have impacted crop yields. Production costs have increased in accordance with South Africa’s consumer price index whereas selling price has moved with the less inflationary global platform. Together, these have made the industry less economically viable. This has led to a need for value addition to sucrose and to eliminate the dependency on a single commodity. Re-positioning of sugar into value-added products has potential to boost the country’s economy by introducing other sources of revenue. Moreover there is a worldwide need to find alternative means to produce petroleum-based fuels and chemicals and bio-based products are being targeted to meet some of this need. A review of the global status shows that there has been value addition in the sugar industry producing mostly ethanol and other commodity chemicals such as surfactants, organic acids and polyols. It is therefore imperative to find sustainable ways of generating value added platform chemicals from sucrose. The quantitative and qualitative study of this project looks at determining the chemicals that should be considered as having the highest potential for value addition from sucrose in a South African context. The project was scoped to focus on chemicals and fuels that can be produced by biological conversions of sucrose. For the quantitative study, a set of 39 chemicals was selected from major studies performed globally on potential bio-based platform chemicals and these catalogued according to a set of criteria. The decision of the chemical/fuel to be studied was based on the gap in the chemical industry. This list comprised of chemicals that were selected in the US department of energy top 10 list in 2004 and 2010 and top 15 chemicals in the EU list in 2015. In addition to these, chemicals that are currently of interest (which were mostly chemicals that can be used as polymers and biofuels) were included to make up the list of 39 chemicals. The selected chemicals then went through a knock out selection where chemicals that cannot be produced with current technology from sugar or via a biological route were eliminated from the list. A quantitative analysis was then done on the remaining chemicals from the knock out stage. A weighting method which considered a series of factors was used to determine the top platform chemicals. The factors used were to identify platform chemicals that are at a high demand (both in South Africa and internationally), chemicals that showed great potential for profitability based on cost, technology readiness level and product yield. The quantitative analysis allowed seven chemicals to be selected. Finally a qualitative study based on interviews with experts in the field was done. Most of this information provided by the experts was supported by several literatures (Taylor, et al., 2015; Villadsen, et al., 2011; Choi, et al., 2015; Jansen & van Gulik, 2014). The qualitative study identified Succinic acid, Lactic acid and Citric acid as the top three chemicals. A techno-economic study was done on succinic acid, one of the most promising platform chemicals identified. The reasons for its selection was because it has a higher performance and it generates less carbon footprint than petroleum based succinic acid, competiveness for niche market, multiple application via BDO and PBS and its overall favourable environmental process that uses up carbon dioxide from the environment. Firstly, the succinic acid process was designed to be produced using Saccharomyces cerevisiae in a dual phase fed batch fermentation process. The overall design for the succinic acid process was based on the design proposed by Efe, et al (2013). A cost evaluation was then done on the design for an economic analysis. The economic analysis was done on the process to ascertain that there is indeed value addition of sucrose to the platform chemicals chosen. This was done in the form of profitability analysis of the process. An economic analysis of the design shows that the plant is profitable after the first year of operation. The total investment on the plant is R 22.3 billion and the start-up expense is R 1.05 billion. This project serves as a preliminary paper based overview of the general background for the selected platform chemicals that will be researched further in subsequent research.